2022
DOI: 10.3389/fmars.2021.745644
|View full text |Cite
|
Sign up to set email alerts
|

Cladobranchia (Gastropoda, Nudibranchia) as a Promising Model to Understand the Molecular Evolution of Photosymbiosis in Animals

Abstract: Symbiosis with photoautotrophic organisms has evolved in various species and even whole animal lineages, which allowed them to directly benefit from photosynthesis. This so-called photosymbiosis is best studied in cnidarians, which primarily establish symbioses with dinoflagellates from the family Symbiodiniaceae. In most other animals the mechanisms of establishing photosymbiosis, the physiological basis, and the evolution of a photosymbiotic life history remain poorly understood. Sea slugs belonging to the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…This was further confirmed in the sea anemone Aiptasia pallida, where a pharmacogenetic analysis demonstrated that the host's immunity was altered to avoid symbiont rejection [64] and that the host's thrombospondin type 1 repeat (TSR) proteins and lectins, a family of recognition proteins, were involved in the colonization by dinoflagellates [65]. However, a limitation in establishing causal relationships between molecular changes in the host and their impact on the acquisition of symbionts, is that most hosts used in photosymbiosis research are not yet fully genetically tractable [42,66]. The intraspecific diversity related to symbiosis, if any, is often unknown, and genetic crosses are, in most cases, not possible, leading to the intractability of mutations.…”
Section: Genetic Events Underlying Photosymbiont Maintenancementioning
confidence: 99%
“…This was further confirmed in the sea anemone Aiptasia pallida, where a pharmacogenetic analysis demonstrated that the host's immunity was altered to avoid symbiont rejection [64] and that the host's thrombospondin type 1 repeat (TSR) proteins and lectins, a family of recognition proteins, were involved in the colonization by dinoflagellates [65]. However, a limitation in establishing causal relationships between molecular changes in the host and their impact on the acquisition of symbionts, is that most hosts used in photosymbiosis research are not yet fully genetically tractable [42,66]. The intraspecific diversity related to symbiosis, if any, is often unknown, and genetic crosses are, in most cases, not possible, leading to the intractability of mutations.…”
Section: Genetic Events Underlying Photosymbiont Maintenancementioning
confidence: 99%
“…One of the most interesting features of the ecology of the sponges is their potential as hosts for a huge diversity of symbionts (Webster and Thomas 2016). Mutualistic interactions between metazoans and numerous groups of autotrophic organisms have been extensively studied, and appear to be especially relevant in more primitive animal clades, like cnidarians, platyhelminths, certain mollusks and urochordates (Hirose 2015;Jäckle et al 2019;Rosset et al 2021;Rola et al 2022). The importance of symbiotic interactions is particularly important in sponges, and, in fact, it is presumed to be one of the bases of their evolutionary success (Taylor et al 2007a, b), given the presence of cellular receptors of various types on their surface, together with their complex innate immune system (Degnan 2015), elements that facilitate host recognition by their microbial symbionts (Usher 2008).…”
Section: Introductionmentioning
confidence: 99%
“… 16 The striking resemblance between intracellular symbiosis in nudibranchs and corals underscores the potential value of employing nudibranchs as model organisms for investigating the mechanisms underlying coral–algal symbiosis. 17 , 18 Nonetheless, to date, only 2 molecular studies 19 , 20 have been conducted on this subject, leaving much to be uncovered about the symbiotic mechanism. Furthermore, the nudibranch Berghia stephanieae , which was employed in these investigations, is considered to possess a rudimentary symbiotic capacity.…”
Section: Introductionmentioning
confidence: 99%